New approach to calculation of boundary turbulent flow - Мовчан, В. Т.; Романюк, Л. А. (Proceedings of National Aviation University (archive), 2000)
Considered is a simple digital method of boundary turbulent flow calculation. The basis for the method is algebraic model of the type "kinetic energy of turbulence" in which, instead of the additional approximate differential equation, used are intrinsic approximate analytical dependencies The comparison of the received data with the results of other authors’ experiments proved the efficiency of the method, also its possibility to authentically predict development of turbulent flows and their possible separation